Experimentelle Untersuchung der Leberperfusion mit nichtdiffundierenden Radiotracern: Differenzierung der arteriellen und portal-venösen Perfusionskomponente durch Dekonvolutionsanalyse von First-Pass-Zeitaktivitätskurven - Szabö, Z.; Torsello, G.; Reifenrath, C.; Porschen, R.; Vosberg, H. (Nuklearmedizin - NuclearMedicine, 1988)
The transfer function of the liver perfusion is an idealised time-activity curve that could be registered over the liver if a non-diffusible tracer would be injected directly into the abdominal aorta and no tracer recirculation would occur. The reproducibility of the transfer function was experimentally investigated in foxhounds. Both the routes of tracer application and the modes of data evaluation were varied and the perfusion was investigated under physiological and pathological conditions. The transfer function was calculated by deconvolution analysis of first-pass time-activity curves using the matrix regularisation method. The transfer function showed clearly distinguishable arterial and portal-venous components. Repeated peripheral venous and central aortic applications resulted in reproducible curves. In addition to the arterial and portal-venous components the subcomponents of the portalvenous component could also be identified in the transfer function after ligation of the appropriate vessels. The accuracy of the mathematical procedure was tested by computer simulations. The simulation studies demonstrated also that the matrix regularisation technique is suitable for deconvolution analysis of time-activity curves even when they are significantly contaminated by statistical noise. Calculation of the transfer function of liver perfusion and of its quantitative parameters seems thus to be a reliable method for non-invasive investigation of liver hemodynamics under physiological and pathological conditions.